Earth system science : from biogeochemical cycles to global change - Jacobson, Michael C.; Charlson, Robert J.; Rodhe, H.; Orians, Gordon H. (International geophysics series, 2000)
Over the last decade, the study of cycles as a model for the earth's changing climate has become a new science. Earth Systems Science is the basis for understanding all aspects of anthropogenic global change, such as chemically forced global climate change. The work is aimed at those students interested in the emerging scientific discipline. Earth Systems Science is an integrated discipline that has been rapidly developing over the last two decades. New information is included in this updated edition so that the text remains relevant. This volume contains five new chapters, but of special importance is the inclusion of an expanded set of student exercises. The two senior authors are leading scientists in their fields and have been awarded numerous prizes for their research efforts. * First edition was widely adopted * Authors are highly respected in their field * Global climate change, integral to the book, is now one of the most important issues in atmospheric sciences and oceanography.